Angiotensin Converting Enzyme Levels In Ischemic Cerebrovascular Disorders: A Case-Control Pilot Study In North Indian Population - JASPREET KAUR; SARIKA ARORA; BHAWNA SINGH; LAL C THAKUR (International Journal of Pharma and Bio Sciences, 2011)
Background: Experimental studies in lower animals indicate that high plasma levels of angiotensin converting enzyme (ACE) contribute to development of vascular diseases. The level of serum ACE was determined in cerebrovascular disorders [stroke and transient ischemic attack (TIA)]. Method: The present cross-sectional study was carried out on 50 cases of stroke and 10 cases of TIA with 60 controls matched for age and sex. Serum angiotensin converting enzyme was estimated by spectrophotometric measurement using the synthetic tripeptide substrate ( N-(3) (2 - furyl )adroyloyl ) –L- phenylalanylglycyl glycine(FAPGG). The levels of ACE were correlated with severity and outcome of stroke. Result The level of serum ACE were significantly higher in stroke (27.50 ± 1.14U/L) and TIA (31.60 ±2.02 U/L) as compared to controls (22.61± 0.79 U/L). Higher levels of ACE showed positive correlation with severity of disease and poorer outcome. Conclusion Levels of serum ACE increase significantly in stroke and TIA patients and is associated with increased severity and worse outcome of cerebrovascular diseases.